A STUDY ON THE ABILITY OF ENGLISH STUDY PROGRAM STUDENTS IN IDENTIFYING PASSIVE VOICES - Hariani, Putri Shara; Supriusman, Supriusman; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This descriptive research aimed to find out the ability of English Study Program students in identifying passive voice. The population of the study was the second-year students of the English study program FKIP Universitas Riau. The sample was 39 participants selected by cluster random sampling technique. The instrument of the research was used a multiple-choice test which consists of 30 items. The instrument of the research consists of 6 tenses of passive voices including the simple present tense, present future tense, simple past tense, present perfect tense, present continuous tense, and modals. After calculating by using a quantitative method, students’ ability was highest in the form of simple present tense with a means score of 73.3 and is categorized into a good level and low score in the form of past tense with a means score of 40.5 and is categorized into a poor level. Overall, the result showed that students’ ability in identifying passive voices was at a mediocre level with mean score was 58. The finding implied that the second-year students of English Study Program FKIP Universitas Riau should improve their ability in understanding the formula of passive voices and the kinds of each tense to reach an excellent level.Keyword: Students’ Ability, Identifying, Passive Voices